Proceedings of the Symposium on Applied Computing 2017
DOI: 10.1145/3019612.3019704
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria optimization in distributed micro-conveying platform

Abstract: In this paper, we study the optimal use of a conveying surface, called smart surface, using distributed microrobotic system that is designed to manipulate fragile micro objects. The smart surface is composed of a 2D array of decentralized micro-modules. Each micro-module is composed of a microactuator, a microsensor, computing and communication units. The cooperation among these micro-modules allows the micro-object to be accurately located and moved on the surface. We discuss in this paper the algorithmic sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Regarding the authors' previous research, an initial study can be found in (19). The work presented here presents a more realistic modeling and a significant extension of the precedent study.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the authors' previous research, an initial study can be found in (19). The work presented here presents a more realistic modeling and a significant extension of the precedent study.…”
Section: Related Workmentioning
confidence: 99%
“…In (19), we proposed a synchronous algorithm which avoids the drawbacks above. Each block stores three scalar values corresponding to its RU L, T and next.…”
Section: Massively Distributed Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…For a surface with gradient θ, (12) is updated to (10b) by replacing R with R/sinθ in (12). The division by sinθ defines the radius of curvature in terms of its projection on the horizontal plane.…”
Section: Micropart Motion Tracking On Surface a Estimation Of State Updatingmentioning
confidence: 99%
“…• Part handling workcells: These workcells, comprising of an array of actuators, are used to translocate the part at the required location. Various types of actuators are used on these workcells including ultrasonic [6], thermobimorph [7], compressed air nozzles [8], air-levitated electrically driven platforms [9], electrostatic attractionrepulsion mechanisms [10], micro-conveyor comprising of discrete microblocks containing microcontroller, sensors and microactuators [11], [12], and a conveyorbased bridge resonator driven by linear traveling waves with the support of 3D printed legs [13]. A concept of controlling the motion of multiple objects on a Chladni plate is presented in [14], however, no model discussing the interaction of microscale forces between particle and surface is presented.…”
Section: Introductionmentioning
confidence: 99%